Muscle atrophy in polytraumatized patients – a longitudinal observational pilot study - Teves, Danjana; Pastor, Torsten; Pastor, Tatjana; Ganse, Bergita (Frontiers in Physiology, 2025)
In polytraumatized patients, muscle atrophy appears more pronounced than in immobilized healthy study participants. However, rates and trajectories of the acute muscle atrophy and associated parameters have not been reported. In a prospective longitudinal pilot study with 10 patients (Injury Severity Score (ISS) ≥16), hand grip strength and inflammatory blood parameters were assessed. Skeletal muscle thickness of the rectus femoris (RF), vastus lateralis (VL), and tibialis anterior (TA), and subcutaneous tissue thickness over these muscles were measured via ultrasound. Muscle oxygen saturation (SO2), relative haemoglobin content (rHb), blood flow (BF), and blood flow velocity (BFV) were captured by laser-Doppler and white-light spectroscopy. Three women and seven men were included (age 43.2 ± 22.5 years; height 176.4 ± 5.7 cm; body weight 83.0 ± 14.5 kg; ISS 24.5 ± 4.6 points). Hand grip strength increased (p < 0.001) at a rate of 0.85%/d. Muscle thickness decreased (p < 0.001) at rates of −0.47%/d (RF), −0.39%/d (VL), and −0.38%/d (TA); no difference in the rate of decline between muscles (p = 0.908). Recovery of VL thickness was observed between the third and fourth week (p = 0.016). There were no changes in subcutaneous tissue thickness. Muscle perfusion parameters SO2, rHb, BF and BFV showed high variability with significant time effects only in the rHb of the TA (p = 0.003). CRP and leukocyte count decreased (both p < 0.001). Unexpectedly, grip strength increased despite a reduction in muscle thickness, likely after decreasing compared with pre-injury. Possible reasons are discussed.